Precipitation Drives Frugivory in a Subtropical Generalist Herbivore, the Gopher Tortoise, and Alters Its Functional Role as a Seed Disperser - Figueroa, Adrian; Chernyavskiy, Pavel; Greenacre, Michael; Herrera, Alyssa; Cuni, Lydia; Villate, Jennifer; Galetti, Mauro [UNESP]; Liu, Hong; Whitfield, Steven (Wiley, 2024)
Consumers employ a variety of foraging strategies, and oftentimes the foraging strategy employed is related to resource availability. As consumers acquire resources, they may interact with their resource base in mutualistic or antagonistic ways—falling along a mutualism-antagonism continuum—with implications for ecological processes such as seed dispersal. However, patterns of resource use vary temporally, and textbook herbivores may switch foraging tactics to become more frugivorous in periods of greater fleshy fruit availability. In this study, we investigated how fleshy fruit consumption of a generalist herbivore—the gopher tortoise (Gopherus polyphemus)—shifts intra-annually following seasonal precipitation and subsequently examined how this shift toward increased frugivory influences the suite of plant syndromes dispersed. We noted a clear intra-annual shift toward a more frugivorous diet which coincided with seasonal precipitation and subsequently observed a marked shift in the plant syndromes dispersed with increasing frugivory. We found that as this generalist herbivore became more frugivorous, it dispersed a greater variety of plant syndromes at low levels of frugivory. However, when the gopher tortoise exhibited high levels of frugivory, the seed load was dominated by those exhibiting the endozoochory syndrome. This study illustrates a functional shift in a seed-dispersing herbivore toward that of a classical frugivore, suggesting that temporal variation in foraging strategy and the temporal scale in which foraging habits and seed dispersal interactions are quantified have implications for the suite of plant syndromes species disperse. Furthermore, trade-offs may exist that provide plants with the endozoochory syndrome with a competitive advantage over seeds with contrasting traits, such as the foliage is the fruit syndrome which is expected to experience greater dispersal by classical herbivores.
Keywords: frugivory; gopher tortoise; herbivory; mutualism; plant–animal interactions; seed dispersal